Carotid Artery Remodeling Is Segment Specific: An In Vivo Study by Vessel Wall Magnetic Resonance Imaging. Issue 4 (April 2018) - Watase, Hiroko; Sun, Jie; Hippe, Daniel S.; Balu, Niranjan; Li, Feiyu; Zhao, Xihai; Mani, Venkatesh; Fayad, Zahi A.; Fuster, Valentin; Hatsukami, Thomas S.; Yuan, Chun
Abstract : Objective—: Early atherosclerosis is often undetected due in part to compensatory enlargement of the outer wall, termed positive remodeling. Variations in hemodynamic conditions and clinical factors influence the patterns of remodeling. The carotid artery provides an opportunity to examine these variations because of the unique geometry of the carotid bulb. This study aimed to determine differences in remodeling of the common, internal, and bifurcation segments of the carotid using magnetic resonance imaging. Approach and Results—: Carotid arteries of 525 subjects without history of cardiovascular disease were imaged by magnetic resonance imaging. The carotid artery was divided into 3 segments: common carotid artery; bifurcation; and internal carotid artery. Remodeling patterns were characterized using linear regression analysis of lumen and total vessel areas (dependent variables) compared with maximum wall thickness (independent variable) for each segment, adjusted for age, sex, and height. The common carotid artery demonstrated a pattern consistent with positive remodeling, whereas the bifurcation demonstrated negative remodeling. The internal carotid artery demonstrated a mixed pattern of outer wall expansion and lumen constriction. Females and subjects with diabetes mellitus showed more positive remodeling, hypertension was associated with attenuated positive remodeling, and those with hypercholesterolemia showed more negative remodeling. Conclusions—: In this cohort of 55- to 80-year-old individuals without history of cardiovascular disease, the pattern of early carotid artery remodeling was segment specific and appeared to be associated with sex and clinical characteristics. These findings provide the groundwork for longitudinal studies to define local and systemic factors such as hemodynamic and clinical conditions on carotid artery remodeling. Abstract : Supplemental Digital Content is available in the text.